2021
DOI: 10.1111/rda.14022
|View full text |Cite
|
Sign up to set email alerts
|

Thymus satureioides and Origanum majorana essential oils improve the quality of Beni Arouss buck semen during storage at 4°C

Abstract: This study aims to investigate the effects of essential oils (EOs), extracted from Thymus satureioides (TS) and Origanum majorana (OM), on Beni Arouss buck semen quality stored in skimmed milk at 4°C. EOs were extracted by hydro‐distillation, and the chemical compounds were determined. Ejaculates were collected from six Beni Arouss bucks, once a week for 10 weeks, and they were pooled, divided into five equal aliquots and diluted to 400 × 106 sperm/ml with skimmed milk supplemented with 0.01% of OM EO, 0.01% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This toxicity is probably due to the interaction of hydrophobic molecules of OM EO with phospholipids and proteins in sperm membranes, which could adversely affect its morphology and membrane permeability and integrity (Chikhoune et al, 2015). Several studies have reported the harmful effect of EOs on semen quality with concentrations above 0.03%, such as OM (Kchikich et al, 2021), and Thymus munbyanus (Chikhoune et al, 2015). Motility, live sperm, morphology and membrane integrity are of fundamental importance in assessing sperm quality (Pande & Srivastava, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This toxicity is probably due to the interaction of hydrophobic molecules of OM EO with phospholipids and proteins in sperm membranes, which could adversely affect its morphology and membrane permeability and integrity (Chikhoune et al, 2015). Several studies have reported the harmful effect of EOs on semen quality with concentrations above 0.03%, such as OM (Kchikich et al, 2021), and Thymus munbyanus (Chikhoune et al, 2015). Motility, live sperm, morphology and membrane integrity are of fundamental importance in assessing sperm quality (Pande & Srivastava, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of skim milk supplemented by 0.02% of OM EO on motility, viability, morphology and integrity could be due to the antioxidant properties of terpinene-4ol (31.18%), γ-terpinene (17.68%) and α-Terpinene (12.69%) which are the main components of OM EO (Kchikich et al, 2021). Previous studies highlighted that the inclusion of different protective agents, such as tocopherols, glutathione (Sarangi et al, 2017) and phytoextracts (Kchikich et al, 2021) with antioxidant properties, is suitable to improve total and progressive motility, viability, integrity, morphology and lipid peroxidation. Correlation results for treatments without antibiotics revealed that lipid peroxidation level was negatively correlated with motility, viability, integrity and positively with sperm abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of essential oils with 31% carvacrol has also been evaluated on buck semen, where a concentration of 0.01% of essential oil had a beneficial effect on the preservation of semen stored at 4°C (Kchikich et al, 2021). Additionally, this molecule has been studied as an antibiotic in boar semen, with a concentration-dependent effect on sperm motility (Frydrychová et al, 2012).…”
Section: Introductionmentioning
confidence: 99%